Evaluation of Nickel, Copper, and Cadmium Contamination in Sediments from The Waters of Mare Island, North Maluku - Andi Budi Bakti; Muhammad Yudhistira Azis; Halikuddin Umasangaji; Diyah Fatimah Oktaviani; Prasetyo Abi Widyananto (Fisheries and Marine Science Faculty - Jenderal Soedirman University, 2025)
Mare Island has been appointed as a conservation area and tourist park due to its seagrass, coral reef, and mangrove ecosystems. However, intensive nickel mining activities in Maluku have the potential to contaminate the marine environment. Heavy metals resulting from these activities are toxic and harmful to both human and marine biota health. Monitoring of the marine environment is important through sediment quality assessment. Therefore, this study aims to evaluate contamination of Ni, Cu and Cd in sediments from the waters of Mare Island, using verified testing methods. The sediment samples were wet-digested using aqua regia on a hotplate and analyzed using flame atomic absorption spectrophotometer (FAAS). The testing method was verified according to AOAC guidelines, covering linearity, LOD, LOQ, recovery, and repeatability. The results show that the concentrations of Ni, Cu, and Cd in the waters of Mare Island ranged from 23.30–29.30; <0.51–5.21 and 6.20–7.94 mg/kg dw, respectively. The Cu concentration is still within safe limits, while Ni and Cd concentrations are categorized as hazardous, posing a risk to marine biota. Based on Contamination Factor, Enrichment Factor, Pollution Load Index, and Potential Ecological Risk Index values, the waters of Mare Island are classified as polluted, originating from anthropogenic activities.